2022
DOI: 10.3390/ani12060775
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sick and Dead Pig Waste Recycling—A Case Study of Hebei, Shandong, and Henan Provinces in China

Abstract: Improper handling of sick and dead pigs may seriously affect public health, socio-economic conditions, and eventually cause environmental pollution. However, effective promotion of sick and dead pig (SDP) waste recycling has become the prime focus of current rural governance. Therefore, the study explores the impact of commitment, rewards, and punishments to capture the recycling behavior of farmers’ sick and dead pig waste management. The study employs factor analysis, the probit model, and the moderating eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…However, some studies, for example Knockaert et al [ 30 ] and Zhang et al [ 31 ], suggest that these mechanisms may impact farmer’s attitudes and subjective norms as mediators. Interestingly, among the various studies of the Chinese livestock industry, most researchers (e.g., Ge et al [ 32 ], Si et al [ 33 ], and Wang and Tao [ 34 ]) have observed that enabling an environmentally friendly waste management revolution is likely to be primarily influenced by governmental disincentive and incentive mechanisms. The present study adopts the variables and core model presented by Ge et al [ 32 ] and modifies these in relation to the context of the study.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some studies, for example Knockaert et al [ 30 ] and Zhang et al [ 31 ], suggest that these mechanisms may impact farmer’s attitudes and subjective norms as mediators. Interestingly, among the various studies of the Chinese livestock industry, most researchers (e.g., Ge et al [ 32 ], Si et al [ 33 ], and Wang and Tao [ 34 ]) have observed that enabling an environmentally friendly waste management revolution is likely to be primarily influenced by governmental disincentive and incentive mechanisms. The present study adopts the variables and core model presented by Ge et al [ 32 ] and modifies these in relation to the context of the study.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…Interestingly, among the various studies of the Chinese livestock industry, most researchers (e.g., Ge et al [ 32 ], Si et al [ 33 ], and Wang and Tao [ 34 ]) have observed that enabling an environmentally friendly waste management revolution is likely to be primarily influenced by governmental disincentive and incentive mechanisms. The present study adopts the variables and core model presented by Ge et al [ 32 ] and modifies these in relation to the context of the study. In the following section, we outline the theoretical perspective and major components of the framework.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations